Genetic Linkage Map of Cassava (Manihot esculenta Crantz) Based on Rubber Tree and Cassava Simple Sequence Repeat Markers - Supajit Sraphet (2018)
© 2016 Taylor & Francis. A total of 1,156 rubber tree (Hevea brasiliensis Muell. Arg.) expressed sequence tags derived simple sequence repeat (EST-SSR) primer pairs were tested for cross-genera transferability with two cassava and three rubber tree cultivars. Amplification products were generated from cassava genomic DNA with 384 primer pairs. Of these, 16 markers showed informative polymorphisms between the two cassava cultivars (Huay Bong 60 and Hanatee) and these were subsequently integrated with 510 previously characterized cassava SSR markers to construct a genetic linkage map. The final map comprised 519 markers (10 rubber tree SSRs and 509 cassava SSRs) distributed across 21 linkage groups covering 1,542.9 cM, with a mean between-marker distance of 5.04 cM. The application of transferable rubber tree SSRs to the development of cassava genetic linkage maps will aid in quantitative trait loci (QTL) mapping in cassava and facilitate comparative genome studies between the two plant species in the future.